2021
DOI: 10.2478/nuka-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary computational and experimental design studies of the ISHTAR thermostatic rig for the high-temperature reactors materials irradiation

Abstract: The Irradiation System for High-Temperature Reactors (ISHTAR) thermostatic rig will be used to irradiate advanced core material samples in conditions corresponding to those prevailing in the high-temperature reactors (HTRs): these conditions include a stable temperature extending up to 1000°C in the helium atmosphere. Computational and experimental studies concerning the design have been conducted, proving the possibility of these conditions’ fulfillment inside the rig while maintaining the safety limits for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The ISHTAR device was tested with the use of special hydraulic stand, and the first batch of measurements confirmed that we can achieve 1000 • C [34] inside the capsule. Since August 2021 it has been installed in the core and successfully operated for three consecutive reactor operational cycles [35].…”
Section: Horizontal Channelsmentioning
confidence: 82%
“…The ISHTAR device was tested with the use of special hydraulic stand, and the first batch of measurements confirmed that we can achieve 1000 • C [34] inside the capsule. Since August 2021 it has been installed in the core and successfully operated for three consecutive reactor operational cycles [35].…”
Section: Horizontal Channelsmentioning
confidence: 82%
“…Although presently built generation III/III+ NPPs are much improved as compared to previous projects, generation IV (Gen-IV) initiative calls for new nuclear energy systems that will significantly improve the safety and reliability, sustainability, useful reactor life, proliferation-resistance, and profitability [5]. Generation-IV International Forum (GIF) members identified six systems [6]: very high temperature gas-cooled reactors (VHTR) [7,8], gas-cooled fast reactors (GFR) [9], sodium-cooled fast reactors (SFR) [10,11], lead-cooled fast reactors (LFR) [12], molten salt reactors (MSR) [13], and super-critical water-cooled reactors (SCWR) [14]. However, the Gen-IV projects typically pose new material challenges.…”
Section: Introductionmentioning
confidence: 99%